Glycosaminoglycan: a candidate to stimulate the repair of chronic wounds - Peplow, Philip V. (Thrombosis and Haemostasis, 2005)
A persistent inflammation with large numbers of neutrophils is found in chronic wounds. Secretory products released from the neutrophils, which include proteinases and a heparin-binding protein, are detrimental to wound healing as they cause degradation of the extracellular matrix and growth factors, and promote further recruitment of neutrophils to the wound area. The neutrophil-derived elastase, cathepsin G, proteinase-3 and heparin-binding protein are cationic, and it is hypothesized that their effects can be inhibited by electrostatic binding with certain anionic polymers such as glycosaminoglycans or functionalized dextrans. A sustained delivery of such compounds alone or in combination from a biodegradable carrier may provide a stimulus for these wounds to pass to the next stage of repair.
Keywords: Wound healing; chronic wounds; inflammation; glycosaminoglycan; anionic polysaccharide